Hypervalent Iodine-Mediated Diastereoselective α-Acetoxylation of Cyclic Ketones - Tan, Jiashen; Zhu, Weiqin; Xu, Weiping; Jing, Yaru; Ke, Zhuofeng; Liu, Yan; Maruoka, Keiji (Frontiers in Chemistry, 2020)
A binary hybrid system comprising hypervalent iodine(III) reagent and BF3•OEt2 Lewis acid was found to be effective for the diastereoselective α-acetoxylation of cyclic ketones. In this hybrid system, BF3•OEt2 Lewis acid allowed the activation of hypervalent iodine (III) reagent and cyclic ketones for the smooth alpha-acetoxylation reaction, achieving high diastereoselectivity. This hypervalent iodine mediated α-acetoxylation of cyclic ketone reaction plausibly undergoes an SN2 substitution mechanism via α-C-bound hypervalent iodine intermediate. The diastereoselectivity of the reaction is mainly originated from thermodynamic control.